The Impact of Study Skills Training and Multiple Intelligence Interventions on The Reading Habits of Junior Secondary School Students - Lasisi, Adekola Kamil; Bukola Abdulmajeed, Kaothar (Universitas Mercu Buana Yogyakarta, 2024)
This study examined the impact of study skills training and multiple intelligence interventions on students in junior secondary schools’ reading habits in Ilorin West LGA. The main purpose was to investigate the impact of study skill training and multiple intelligence interventions on students' reading habits other specific purposes were stated. The population of this study include all the junior secondary school students in Ilorin West LGA. Meanwhile, the study purposefully selected a sample of 64 JSS II students from 4 schools. In line with the purposes, seven hypotheses were formulated. The instruments used for the study were an adopted questionnaire on study skills and multiple intelligence intervention, data collected was analysed using Analysis of Co-variance (ANCOVA) and T-test statistical tools at 0.05 level of significance. Results of the findings revealed the significant effect of study skills training and multiple intelligence interventions on the reading habits of junior secondary school students in Ilorin West LGA. The interventions positively impacted students' reading engagement and practices, highlighting the potential of tailored educational strategies to enhance academic behaviours.